Human Antibody Response Against Anopheles gambiae Salivary Proteins - Luckert, Meagan; Rozo, Paula; Londono, Berlin (My University, 2017)
Malaria is a life-threatening disease caused by parasites that are transmitted to people through the bites of infected female Anopheles mosquitoes. There are more than 400 different species of Anopheles mosquitoes; however only 30 are major malaria vectors. Anopheles vector species bite between dusk and dawn. During blood feeding, the female mosquito injects saliva into the human skin to facilitate meal intake. The salivary proteins (mSP) stimulate immune responses that may lead to antibody production. It is hypothesized that in endemic settings, after repeated mosquito bites, human hosts develop an immune response against mSP that correlates with the level of exposure.